The development of a tournament preparation framework for competitive golf: A Delphi study - Pilgrim, J.; Kremer, P.; Robertson, S. (European Journal of Sport Science, 2018)
Tournament preparation in golf is used by players to increase course knowledge, develop strategy, optimise playing conditions and facilitate self-regulation. It is not known whether specific behaviours in tournament preparation should be given priority in education and practice at different stages of competition. This study aimed to achieve consensus on the importance of specific tournament preparation behaviours or "items" to players of five competitive levels. A two-round Delphi study was used, including an expert panel of 36 coaches, high-performance staff, players and academics. Participants were asked to score the relative importance of 48 items to players using a 5-point Likert-type scale. For an item to achieve consensus, 67% agreement was required in two adjacent score categories. Consensus was reached for 46 items and these were used to develop a ranked framework for each competitive level. The developed framework provides consensus-based guidelines of the behaviours that are perceived as important in tournament preparation. This framework could be used by national sport organisations to guide the development of more comprehensive learning environments for players and coaches. It could also direct future studies examining the critical behaviours for golfers across different competitive levels.